Proposta de renovação do Museu de Escultura Comparada de Mafra : nos seus aspetos de conservação e curadoria - Figueiredo, Bárbara Cabrita Freire da Cruz Vidigal de (2019)
This dissertation is dedicated to the investigation of the Museum of Comparative Sculpture at Mafra, Portugal. Since February 28th, 1964 the National Palace of Mafra (PNM) has displayed in chronological order a collection of plasters with Portuguese, French and some Italian references across nine rooms. The collection from various origins, institutional and other, got the official name of the Museum of Comparative Sculpture. This gipsoteca, of a didactic and appealing character founded by Diogo de Macedo (1889-1959), overcame several obstacles until its materialization at Mafra, providing an enjoyable continuity to the Sculpture School (1753) with its expositive course. Despite several attempts of its operation until 1974, the PNM found itself helpless due to financial cuts, opting for the current system of only opening the doors to those who make a reservation. The Museum ended up as an unfortunate museological case that has not been divulged, nor properly used for more than forty years. The plaster copies are not mere monumental and tomb copies, as they preserve in themselves the lost form of their original figures using an extinct traditional technique, the execution of tacelos. The exhibition also exemplifies the 60s way of thinking in museology. Today this capsule preserved in time is threatened by its aggravated state, caused not only by the lack of maintenance of the pieces, but also of the building itself, although prejudice for the rough lines of the technique and the lack of originals also resulted in neglect and lack of interest in investing in it. With this study we intend to provide visibility to the current state of this Museum of Comparative Sculpture, make its material and immaterial patrimony known, while simultaneously providing a critical and updated reflection and a new curatorial view based on conservative and museological notions as a contribution to a possible reopening